The Mystery Of Holly Lane - Blyton, Enid (London Egmont / Eurokids International Ltd, 2009)
The Five Find-outers have got 15 thrilling mysteries to solve. Join Fatty, Larry, Daisy, Pip, Bets and Buster the dog in puzzling out these riddles.
Keywords: Children's Literature - Fiction : Detective / Mystery